2020
DOI: 10.7861/clinmed.2019-0183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a pilot process for reviewing late HIV diagnoses in England and Wales

Abstract: Late HIV diagnosis is associated with signifi cant mortality in people living with HIV (PLWH) and high numbers of missed opportunities (MO) for earlier testing have been identifi ed. A pilot of a national late diagnosis review process (LDRP) was undertaken in 15 HIV services evaluating the feasibility of LDRP implementation, as a patient safety initiative. All newly diagnosed PLWH with CD4 counts <200 cells/mm 3 were included, and healthcare episodes within 5 years of presentation reviewed. Of 127 patients ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…We aimed to quantify the risk of in-ICU mortality among people with HIV associated with and attributable to late The persistent problem of late diagnosis and its association with an increased risk of mortality among people with HIV in general is well documented [8,21,22,[34][35][36][37]. A 10-year study using data collected between 1999 and 2008 from a national cohort of people with HIV in England and Wales estimated that 60% of all-cause mortality was attributable to late diagnosis [38].…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to quantify the risk of in-ICU mortality among people with HIV associated with and attributable to late The persistent problem of late diagnosis and its association with an increased risk of mortality among people with HIV in general is well documented [8,21,22,[34][35][36][37]. A 10-year study using data collected between 1999 and 2008 from a national cohort of people with HIV in England and Wales estimated that 60% of all-cause mortality was attributable to late diagnosis [38].…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to include the experience of medical professionals and their views of things that might help. Two main suggestions from a large BHIVA audit in 2016 were to (i) expand coverage of HIV in medical training and inductions and in grand round discussions and (ii) to expand HIV testing more broadly when commissioning services [16, 17].…”
Section: Common Reasons For Late Diagnosismentioning
confidence: 99%
“…Analyses of very late diagnoses in England and Wales found that approximately 60% of missed opportunities for testing occurred in primary care and approximately 30% in secondary care. 57 , 58 In the hospital setting, high staff turnover, competing clinical priorities, and confusion around consenting procedures may contribute to missed opportunities for diagnosis. 55 Peers encouraging best practice and the provision of up-to-date information to physicians via trusted sources (e.g.…”
Section: Prevalence Of Late Hiv Diagnosis In the Uk And Patient Chara...mentioning
confidence: 99%
“… 61 Treating missed opportunities for HIV diagnosis as a patient safety issue in cases of patient death may also facilitate individual and institutional learning. 57 …”
Section: Prevalence Of Late Hiv Diagnosis In the Uk And Patient Chara...mentioning
confidence: 99%
See 1 more Smart Citation